DO LABORATORY BIOMARKERS PREDICT SURVIVAL IN SEVERE COVID-19? A CROSS-SECTIONAL STUDY - Bahadur, Sher; Rahim, Fawad; Amin, Said; Noor, Mohammad; Gul, Huma; Mahmood, Afsheen; Usman, Muhammad; Ullah, Raza; Khan, Muhammad Asif; Shahab, Khalid (Journal of Ayub Medical College Abbottabad, 2022)
Background: This study aims to compare lymphocyte count, C-reactive protein (CRP), ferritin, Lactate Dehydrogenase (LDH) and D-dimer among survivors and non-survivors of severe COVID-19. Methods: This retrospective cross-sectional analytical study included 69 patients for whom a record of the biomarkers and survival status was available. Baseline and peak values were selected for serum CRP, ferritin, LDH and D-Dimer. Baseline and trough lymphocyte counts were selected. Data were analyzed using SPSS version 21. Mean and standard deviation were used to compare the biomarkers with paired t-test. p-value <0.05 was taken as significant. Results: The mean age of the study population was 55.5±9.1 years and 50 (72.5%) were male. Among survivors, the increase in CRP level was not significant (from 15.80±9.8 mg/dl to 17.87±8.4 mg/dl, p=0.45) while it was significant in non-survivors (from 16.68±10.90 mg/dl to 20.77±12.69 mg/dl, p=0.04). There was no significant rise in LDH levels in survivors (from 829.59±499 U/L to 1018.6±468 U/L, p=0.20) while it increased significantly in non-survivors (from 816.2±443.08 U/L to 1056.61±480.54 U/L, p=0.003). The decrease in lymphocyte count and increase in D-Dimers in both the groups was significant (p=0.001). There was no significant elevation in ferritin in both the groups (p>0.05). Conclusion: In severe COVID-19 patients, serum CRP and LDH can be used for risk stratification and predicting survival. Lymphopenia, increase in serum ferritin and D-dimers may not predict survival.